USE OF TECHNOLOGY GLOBAL POSITIONING SYSTEM (GPS) RECEIVER GARMIN ETREX VISTA AS A TOOL NAVIGATION - Paul Jabesh Supit Kilis; Fivtatianti H., SKom. MM Fivtatianti H., SKom. MM (Jurnal Sistem Komputer, 2006)
Global Positioning System (GPS) is a radio system navigation and positioningusing satellites. By using a GPS receiver, we can determine the position of ourexistence. The purpose of this paper is to use a GPS receiver as a navigational tool,which in this study used a GPS receiver is the Garmin eTrex Vista.